Desain External Rotor IPM-V Motor Brushless DC Terhadap Torsi Cogging - Fauzan Rhabbani, Muhammad; Azizul Hakim, Ermanu; Kasan, Nur (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2021)
Internal Permanent Magnet brushless DC motor is one of the various types of electric motors using permanent magnets that are inserted into the rotor's core without having to stick it like a permanent magnet motor mounted on the surface.This motor has better torque characteristics, high efficiency, and sturdy construction. But the consequences in the use of permanent magnets can’t be separated from the interaction between the permanent magnetic field mounted by the rotor with stator teeth. So that development is needed to obtain the results of better cogging torque and efficiency, such as variations in the external rotor IPM-V angular range of 80 °, 90 ° and 100 ° in 18 slots and 16 pole models which are simulated using the Infolytica Magnet application based on Finite Element Method (FEM), the data is processed using Microsoft Excel, so that the output will be a parameter in the Simulink MATLAB 2016a modeling to get the characteristics of the design motor. Variation testing on the motor is done at a speed of 2100 rpm. The results of the test show that the minimum cogging torque value in the angle model of the 90 ° magnetic range is 1.64 Nm with the highest efficiency of 80.6%. Smaller cogging torque values will reduce vibration or noise when the motor is spinning. The high value of efficiency indicates the losses that cause heating on the motor are smaller, so that the motor operating period becomes longer.